2001
DOI: 10.1111/j.1349-7006.2001.tb02137.x
|View full text |Cite
|
Sign up to set email alerts
|

Organotropic Chemopreventive Effects of n‐3 Unsaturated Fatty Acids in a Rat Multi‐organ Carcinogenesis Model

Abstract: Organotropic chemopreventive effects of n-3 unsaturated fatty acids were studied using a multiorgan carcinogenesis model in male rats. Rats were treated with diethylnitrosamine (DEN), Nmethyl-N-nitrosourea (MNU), N-butyl-N-4-hydroxybutylnitrosamine (BBN), 1,2-dimethylhydrazine (DMH) and dihydroxy-di-n-propylnitrosamine (DHPN) during the first 7 weeks, and then given unsaturated fatty acid (UFAs), docosahexaenoic acid (n-3, C 22:6 ) (DHA), eicosapentaenoic acid (n-3, C 20:5 ) (EPA), linoleic acid (n-6, C 18:2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…In chemically induced carcinogenesis models, compared with oleic acid-treated male rats, DHA treatment significantly decreased incidence and multiplicity of the colon tumors; EPA treatment tended to decrease incidence and multiplicity, but not significantly (19). In culture, DHA more effectively suppressed the growth of HT-29 human colon adenocarcinoma cells than EPA (20).…”
Section: Discussionmentioning
confidence: 89%
“…In chemically induced carcinogenesis models, compared with oleic acid-treated male rats, DHA treatment significantly decreased incidence and multiplicity of the colon tumors; EPA treatment tended to decrease incidence and multiplicity, but not significantly (19). In culture, DHA more effectively suppressed the growth of HT-29 human colon adenocarcinoma cells than EPA (20).…”
Section: Discussionmentioning
confidence: 89%
“…The reason for the discrepancy with the many previous studies which showed chemopreventive effects on colon carcinogenesis and ACF development [1][2][3][4]27,31,32 , may be due to the different number of treatment times per week. DHA was injected five times a 20,21,23,33 incidences of colon tumor development have been reported to range from 10 to 80%, therefore the figure of 10% achieved in the present study was relatively low. Thus, one reason for the lack of obvious influence of DHA could have been due to weak initiation.…”
Section: Discussionmentioning
confidence: 52%
“…R e c e n t l y , d i f f e r e n t r e s u l t s r e g a r d i n g t h e chemopreventive effect of DHA-E in diet using the same model were published by an other group 33 . They showed an inhibitory effect on carcinogenesis in the small intestine, large intestine and lung by DHA.…”
Section: Discussionmentioning
confidence: 73%
“…Chyou et al (1993) reported that men consuming fish (rich in omega-3) 5 times per week or more were associated with a non-significant reduction of bladder cancer risk than those who eat 1 time per week or less (the RR, 0.67; 95% CI, 0.26-1.67). In a rat multi-organ carcinogenesis model, Toriyama-Baba et al (2001) reported that n-3 unsaturated fatty acids did not affect preneoplastic and neoplastic lesion development in the urinary bladder.…”
Section: Omega-3mentioning
confidence: 98%